Assessment on Power Distribution Network Planning in sub-Saharan Africa - Michael, E. Irechukwu; Michael, N. Irechukwu; Samuel, S. Mushakangoma (IEEE, 2022)
Power system distribution network planning (PSDNP) encompasses several tasks including ensuring sufficient substation capacity and distribution capacity for the end users. Both rural communities and urban dwellers benefit when there is a well-planned distribution network. City power consumers enjoy stable electricity supply and the number of annually connected rural households increases with an efficient planning scheme in place. However, this is not the case in many cities and rural areas in sub-Saharan Africa. Poor distribution network planning by many power utilities has led to the annual energy demand growing at a much higher rate than the number of electrified households in many sub-Saharan African countries. Therefore, this paper discusses challenges faced by power utilities and energy consumers due to poor distribution planning techniques. This paper proposes an implementation plan to address the inefficient planning challenges faced by the rural communities and urban dwellers. After that, a case study is selected in East Africa, and the solutions are applied.